Valor nutricional de la harina de Cyperus rotundus “coquito” y su efecto de la adición en dietas sobre el rendimiento productivo de Cairina moschata” pato Muscovy - Aguilar Aguilar, Yaceni Adaliz (2019)
The research was carried out in the "Nutrimentos Florida SAC" experimental center, located at the Huanchaco road junction and the Evitamiento road, Huanchaco district, Trujillo province, with the objective of determining the chemical composition and effect of Cyperus. rotundus "coquito" on the productive parameters of ducks at 56 days of age. 150 male ducks of the Muscovy race were used, randomly distributed in three treatments, under a completely randomized design, T0: Zinc bacitracin 0.05%, T1: Coquito 0.1%, T2: Coquito 0.2%. The bromatological analysis established that the "coquito" has 88.23%, 6.09%, 8.08% and 4.51% in dry matter, protein, fat and ash respectively. In the total weight gain the T0 (4.12 kg) in relation to T1 (3.53 kg) y T2 (3.72 kg) achieved the highest increase with significant statistical differences (P <0.05). The total food consumption was of 8.54 kg, 8.34 kg and 7.6 kg for T0, T1 and T2 respectively (P> 0.05), also for the feed conversion and percentage of mortality no significant statistical differences between the treatments were calculated. It is concluded that the inclusion of coquito in duck diets does not improve its productive parameters.